Effects of d-isocorydine on mouse vas deferens - SHU Huai-de; HUANG Guo-ping (Acta Pharmacologica Sinica; Vol 7, No 3 (May 1986): Acta Pharmacologica Sinica, 2016)
On isolated mouse vas deferens preparations, d-isocorydine hydrochloride (53-212 microM) enhanced the twitch response to field stimulation. However, 424 microM, caused an inhibition. Yohimbine 0.1 microM had no influence on the action of d-isocorydine. Verapamil-HCl 4-256 microM showed similar actions as that of isocorydine. On electrically induced twitch responses it revealed an excitation at 4-32 microM but an inhibition at 128-256 microM. Paraverine 1.33-85.1 microM exhibited only inhibitory action on the twitch response to field stimulation. Both phasic and tonic contractions of vas deferens induced by norepinephrine and KCl were inhibited by d-isocorydine, papavcrine and verapamil. But the rhythmic contraction triggered by norepinephrine was enhanced by isocorydine. The above-mensioned action was probably nyogenous since.